Legal Protection for Children who are Victims of Sexual Violence - Myharto, Wiend Sakti; Lestari, Riva Noor (IBLAM LAW REVIEW, 2025)
Sexual violence against children constitutes a severe violation of human rights, leaving long-lasting impacts on the victims’ physical well-being, psychological state, and social life. This study examines the legal protection afforded to child victims, encompassing preventive measures, law enforcement actions, and post-incident rehabilitation. The research adopts a normative juridical approach, drawing on statutory analysis, literature review, and case examination. The findings reveal that legal instruments such as Law Number 35 of 2014 on Child Protection and Law Number 12 of 2022 on Sexual Violence Crimes provide a comprehensive framework for safeguarding victims. However, practical implementation remains challenged by limited resources, low public awareness, and the psychological barriers victims face in reporting incidents. The study recommends strengthening inter-agency cooperation, enhancing the quality of victim support services, and maximizing the use of technology in case reporting and handling.